Aspectos socioculturales en el destete de la lactancia materna en niños menores de 2 años. - Lunavictoria Ulloa, Dennys Stalin (2024)
The early weaning of breastfeeding is a relevant topic in infant health, with multiple sociocultural factors influencing mothers' decisions. This research focuses on identifying and understanding these factors and proposing recommendations for nursing staff. The aim is to address this issue from a comprehensive perspective, considering both sociocultural determinants and intervention strategies. An exhaustive literature review was conducted using PubMed, Scielo, Science Direct, and Google Scholar databases. Specific inclusion criteria were applied to select relevant studies. Relevant information was extracted and analyzed, identifying patterns and trends in the sociocultural factors associated with early breastfeeding cessation. A wide range of sociocultural factors influencing early weaning were revealed. These include lack of family and workplace support, cultural myths about breastfeeding, and labor regulations related to maternity leave, among others. Significant differences were observed between communities regarding norms and expectations involved in breastfeeding, affecting mothers' weaning decisions. The research highlights the importance of addressing sociocultural factors in early breastfeeding cessation. It is proposed that nursing staff play a crucial role in educating and supporting mothers throughout the breastfeeding process and in promoting workplace policies that support breastfeeding. These measures can promote prolonged breastfeeding and improve children's short- and long-term health and well-being.